Curriculum Design: Difficulties and Realities in Introducing Innovative Teaching and Learning Experience - Abdul Mohaimin Noordin Ayus (The Indonesian Journal of International Clinical Legal Education, 2019)
The 20th century legal education system is said to have failed to teach students practical legal skills, critical analysis and decision-making methods, as it did not give students systematic training in effective techniques for learning the law from the experience of the legal practice. At the end of the century, a pedagogic method known as the clinical legal education was developed which broadens legal education in all of these dimensions. It is important for a member of a law school academic to examine this pedagogical approach towards enhancing students’ knowledge and skills in meeting the needs of the changing time. Law schools in Malaysia and to some extent in Brunei Darussalam have some or limited autonomy in introducing Innovative Teaching and Learning methods into the curriculum design, but no true success could be lauded either as difficulties and realities in the study of law within the common law jurisdictional context requires strong cognitive elements before a student could really delve in practical legal skill exercises. The realities cover two main areas of development: (1) the components of legal studies, and (2) the outcomes of the studies. The difficulties may be associated with (1) the governing educational policies; (2) qualification and quality of students admitted to law school, (3) the experience of the law teachers; and (4) the learning environment. The traditional method could not simply be blamed or ignored, if there ever be a failure in the system, on the one hand, and the much ushered innovative learning methods may not necessarily be the success factor, on the other.